A career in process safety: 50 years of LPS. Issue 1 (5th February 2016) - Dowell, Arthur M. (Art)
Abstract : Drawing from a career from 1963 through 2016 in the chemical and process industries, this article will describe some informal practices of process safety elements observed during the Master‐Apprentice era of the 1960s. The article will trace the development of incident investigation, Process Hazard Analysis, and Fault Tree Analysis tools used by the author. It will touch on safety instrumented systems and the development of Layer of Protection Analysis to determine how strong the safety instrumented functions should be. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 8–12, 2016